Antibacterial activity of bacteriocin produced by Bacillus velezensis BUU004, herb extracts and their combination for controlling spoilage and pathogenic bacteria in dried, seasoned and crushed squid - Nimrat, Subuntith; Soodsawaeng, Pornpimon; Vuthiphandchai, Verapong; Butkhot, Namphueng; Boonthai, Traimat (Science Essence Journal, 2021)
Biopreservation is an attractive measure to maintain the quality and safety of food products simultaneously with fit in healthy lifestyle of consumers. This study aimed to evaluate biopreservative potential of bacteriocin produced by Bacillus velezensis BUU004, a mixture of lemongrass and hot pepper extracts, and their combination for controlling growths of spoilage bacteria and foodborne pathogens in dried, seasoned and crushed squid. The squid samples were treated with 1) sterile distilled water (control), 2) nisin solution, 3) semi-purified preparation containing bacteriocin from B. velezensis BUU004 (SPP-BV), 4) a mixture of lemongrass and hot pepper extracts, and 5) a combination of the SPP-BV and the mixed herb extracts. During 28-day storage, the three types of additives were as effective as commercial nisin for securing biosafety of the dried squid evident by a significant (p<0.05) reduction in total viable count, compared to the control. Administration of the tested additives every 14 days was more effective against spoilage bacteria in dried squid than a single treatment. Then, the tested additives were investigated their antibacterial activity against pathogenic E. coli, Salmonella Typhimurium and Bacillus cereus. The strongest inhibitory effect on all tested pathogens was observed with the combined addition of the SPP-BV and the mixed herb extracts in dried squid. SEM analysis revealed that the three additives had bactericidal activity through destruction of the bacterial cell walls. This study suggested that all tested additives had potential as an alternative for controlling food spoilage and pathogenic bacteria and enhancing the safety of dried seafood products.